The Right to Liberty and Security with Special Regard to Central Europe - Maršavelski , Aleksandar (The ECHR at 70: The Central European Narrative, 2025)
This paper examines the application of the right to liberty and security, as guaranteed by Article 5 of the European Convention on Human Rights (ECHR), within the specific context of Central Europe. Through an analysis of key European Court of Human Rights (ECtHR) case law involving Romania, Poland, Slovakia, Hungary, and Croatia, the study explores the Court's interpretation and enforcement of this fundamental right. The paper delves into critical issues such as the distinction between deprivation of liberty and restriction of movement, the lawfulness and duration of pre-trial detention, procedural safeguards for detainees, and the specific protections afforded to vulnerable groups, including individuals with mental disabilities and asylum seekers. Landmark cases are dissected to illustrate the ECtHR's robust approach to preventing arbitrary detention and ensuring judicial oversight. The analysis reveals the significant impact of the Court's jurisprudence on the domestic legal systems of these post-authoritarian states, highlighting both the progress made in protecting individual liberties and the persistent challenges in balancing state security interests with fundamental human rights. The paper concludes that the ECtHR's role remains indispensable in upholding the principles of the Convention and fostering a common standard of human rights protection across the region. Keywords: Article 5 ECHR, Right to liberty and security, European Court of Human Rights (ECtHR), Central Europe, detention, imprisonment